Social isolation among older people during social distancing throughout the pandemic period of Covid - 19 (PerCursos, 2023)
To analyze the situation of social isolation of older adults during the time of social distancing in the Covid-19 pandemic. Methods: Literature review through bibliographic research, in national and international literature. Data were collected from March 2020 to December 2021, from the Databases available at the Central Library of Brasília (BCE) through remote access to the Capes Periodicals Portal, via the CAFÉ. The final sample consisted of 10 articles. Results: The literature review revealed that the studies have gaps in the conceptualization and theoretical description of social isolation when dealing with the topic in the pandemic period of covid-19. The results of this research pointed to a small number of specific texts related to social isolation in a time of social distance in the Covid-19 pandemic, a clear and objective delimitation was not identified about the difference between social isolation and social distance, being often portrayed as synonyms. In addition, although social distancing is a fundamental measure to prevent the spread of Covid-19 and contain its consequences, and social isolation represents a serious public health problem, the literature reveals that its consequences can be mitigated or even prevented through public power, family and society as a whole in order to overcome its multiple dimensions and impacts. Conclusion: It is concluded that there is a need to use the operational concept of social isolation and its differentiation from social distance measures, in order to highlight the impacts of social isolation due to the Covid-19 pandemic.
Keywords: aging; older adults; social isolation; social distancing